Karakteristik, Proses Keputusan, Difusi, Diseminasi dan Strategi Inovasi Pendidikan - Indra Taupik Saleh; Muhidin Muhidin; Qiqi Yuliati Zakiah; Mohamad Erihadiana; Andewi Suhartini (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Innovation in education is necessary, so that there is a change and provide something new that can improve the quality of education both nationally and internationally. In realizing educational innovation, there is a characteristic that can give color in the innovation itself. And in its implementation requires a decision process that is really mature and not rushed. Before becoming a decision usually the innovation begins from a diffusion that is then organized and systematically designed to be conducted a trial that later turns into dissemination, which is a process in applying innovations that have existing results and considered successful. And success itself requires a strategy so as not to miss the mark and can be used as best as possible, so that the innovation itself really becomes something new and has a positive impact.